MRI-Negative Myelitis Associated With Myelin Oligodendrocyte Glycoprotein Antibody Spectrum Demyelinating Disease. (15th February 2019) - Pérez, Carlos A.; Garcia-Tarodo, Stephanie; Troxell, Regina
Myelin oligodendrocyte glycoprotein is expressed in the central nervous system on the surface of oligodendrocytes and is associated with a broad range of adult and pediatric demyelinating phenotypes. The entire spectrum of clinical and radiologic features of myelin oligodendrocyte glycoprotein antibody spectrum disorder remains to be fully elucidated. We describe the case of a 9-year-old boy with immune-mediated myelitis undetectable by conventional magnetic resonance imaging in the context of relapsing anti-myelin oligodendrocyte glycoprotein spectrum disorder. Despite the severe clinical presentation, his symptoms improved significantly following treatment with corticosteroids. Because timely diagnosis and treatment is imperative to prevent disease recurrence and reduce long-term morbidity, serum anti-myelin oligodendrocyte glycoprotein antibody testing should be considered in all children with acute demyelinating syndromes and unusual clinical presentations—including seizures—both at presentation and at follow-up.